2020
DOI: 10.17718/tojde.690388
|View full text |Cite
|
Sign up to set email alerts
|

E-Collaborative Tasks and the Enhancement of Writing Performance among Iranian University-Level EFL Learners

Abstract: The prevalence of using social software in foreign and second language settings has caused a resurgence of interest in collaborative writing. This study investigates the benefits of collaborative and e-collaborative tasks on writing performance of the students in a process-oriented approach. It, in fact, examines the effects on the accuracy, complexity, and fluency of the written text produced by the learners. To this end, the quasiexperimental design was employed and 74 intermediate students at Islamic Azad U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Such findings are in partial agreement with a study in the literature. For example, Azodi and Lotfi (2020) found that the use of Telegram improved students' internal complexity (particularly their use of subordinate clauses), while their overall complexity remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are in partial agreement with a study in the literature. For example, Azodi and Lotfi (2020) found that the use of Telegram improved students' internal complexity (particularly their use of subordinate clauses), while their overall complexity remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Zioga and Bikos (2020) investigate the effects of using Google Documents as an online collaborative learning tool on writing skills and found that collaborative writings provide constant feedback from peers and teachers, which helps students enhance their critical and conceptual ability. Besides, Azodi and Lotfi (2020) find that online collaborative tasks on writing performance positively contribute to the enhancement of students' cognitive development and motivate them to strive to overcome various problems they face through the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the flipped classroom model is developed pedagogically by using educational technologies to create the most efficient time for class activities. In this approach students can use technological equipment, develop their abilities, create interactive discussion conditions, and discover different learning methods with different learning activities (Ayçiçek & Yelken, 2018).…”
Section: Flipped Learning ( Fl)mentioning
confidence: 99%
“…Koroğlu & Cakır (2017) investigated the effects of flipped instruction on pre-service English language teachers' speaking skills development. Ayçiçek & Yelken (2018) determine the effect of flipped classroom model on students' classroom engagement in teaching English. Ceylaner & Karakuş (2018) investigated the effects of the flipped classroom method on ninth grade students' self-directed learning readiness and attitudes towards the English course and identify how the flipped classroom method affects students' self-directed learning readiness and attitudes towards the English course.…”
Section: Flipped Learning ( Fl)mentioning
confidence: 99%